FAIR AND HUMANE LABOUR PROTECTION: LABOUR PROTECTION POLICIES - Loso Judijanto; Sulaiman; Fitriani Abdullah; Al-Amin (Prosiding Seminar Nasional Indonesia, 2025)
Fair and humane labour protection is one of the crucial aspects in ensuring the welfare of workers in Indonesia. Policies developed through the Employment Law No. 13 of 2003 as well as the Job Creation Law, provide a legal framework that aims to ensure the fulfilment of workers' basic rights such as living wages, social security, and a safe working environment. The government has also undertaken various initiatives, including the Pre-Employment Card programme, to improve the quality of life of the workforce. However, there are still many challenges faced in implementing this policy, especially in the informal sector which has not been fully covered by social security and the imbalance in law enforcement. To overcome these obstacles, stricter law enforcement and effective supervision are needed. In addition, the active involvement of all stakeholders-government, private sector, and labour organisations-will be helpful in creating a more inclusive, fair, and safe working environment. Thus, this collaboration is expected to bring positive changes to the welfare of workers in Indonesia, guarantee their rights, and promote sustainable economic development.